Resveratrol improves endothelial cell markers impaired by plasma incubation from women who subsequently develop preeclampsia - Caldeira-Dias, Mayara [UNESP]; Montenegro, Marcelo F.; Bettiol, Heloisa; Barbieri, Marco Antonio; Cardoso, Viviane C.; Cavalli, Ricardo C.; Sandrim, Valéria C. [UNESP] (Springer Nature, 2019)
In this study, we demonstrated that plasma collected from women who subsequently developed preeclampsia caused increased heme oxygenase-1 (HO-1) production and decreased levels of nitric oxide (NO) markers in endothelial cells (HUVECs). Conversely, no changes in HO-1 or NO markers were found when HUVECs were treated with plasma from women who remained healthy throughout pregnancy. These alterations in HO-1 and NO markers were prevented by cotreatment with the polyphenol resveratrol, which also improved GSH levels. In addition, we evaluated changes induced by plasma incubation in the expression of genes and their related pathways associated with antioxidant defenses, such as Nrf2, ARE activity, and GSR. Collectively, our findings suggest that even before the appearance of clinical symptoms of preeclampsia, plasma from affected women is able to induce modifications in endothelial cells with respect to HO-1 production and NO markers. We believe that this in vitro strategy may offer an attractive alternative to the exploitation of candidate markers or screening molecules, such as resveratrol, for the prevention and management of preeclampsia.
Keywords: Endothelial cells; Plasma; Preeclampsia; Resveratrol